Pengembangan Aplikasi Front-End SIM-MITRA (Sistem Informasi Manajemen Mitra Statistik) BPS Kota Denpasar - Putrawan, Putu Bagus Kresna; Muliantara, Agus (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2019)
Recruitment is the process of finding, finding and attracting capable applicants to be employed in and by an organization. One organization that needs a recruitment process, namely Badan Pusat Statistik (BPS). At present, the need for census officers is needed by BPS to support success in managing data for good quality. In addition, as an organization that also follows developments in communication technology, BPS is also expected to answer the need for fast and easy information acquisition. With these considerations, this study builds a management information system using extreme programming (XP) methods. The plot design is used based on observations and interviews with the Denpasar City's BPS staff. This Statistical Partner Management Information System (SIM-MITRA) application describes the interaction between the user and the system of the application, which each user accesses different features according to the access rights he gets. The software used to build this application system is a data flow diagram, C #, and MySQL as the database. The Management Information System (MIS/SIM in Indonesian) application is expected to help facilitate the input of prospective partner data so that BPS staff will be more effective and efficient in managing the management of statistical partners. The SIM-MITRA application can display partner data forms, assessment forms and recap of partner results received.